Mordedura por Bothrops pictus en paciente adulto de un distrito de Lima: reporte de caso - Atencio Paulino, Joel Isaac (2025)
Snakebites, particularly those from the genus Bothrops spp., represent a public health concern in Latin America due to their high incidence and significant clinical variability. We present the case of a 44-year-old male patient, a gardener by occupation, who was bitten on the left third finger by a snake in Cieneguilla. Initially, no antivenom was available at the nearest health center; therefore, he was transferred to Hospital Edgardo Rebagliati Martins on the same day. Despite receiving immediate medical attention and antivenom treatment upon arrival at the hospital, he developed common local symptoms such as pain, edema, and ecchymosis, but did not exhibit any severe long-term complications. Although the patient did not present with serious complications, the variability in the clinical presentation of snakebites can complicate their management, highlighting the importance of individualized evaluation and treatment. The patient experienced a favorable recovery and was discharged after six days, with no complications. This case points out the importance of prompt medical attention and access to antivenom, especially in areas where snakebites are endemic. In addition, it underscores the need for increased community education on local species and bite prevention, particularly for agricultural workers who face a higher risk. The definitive diagnosis of ophidism caused by Bothrops pictus, recorded in the medical history, was made based on the characteristic clinical presentation, laboratory findings, the snake’s features described by the patient, and the geographic-epidemiological characteristics.